Long-term stability of bronchial responsiveness to histamine. Issue 4 (April 1982) - Juniper, E F; Frith, P A; Hargreave, F E
Abstract : Bronchial responsiveness to histamine was measured in 35 adult asthmatics whose symptoms were controlled on a minimum of medication. The tests were carried out on two occasions separated by 10-30 months. On each occasion the subjects had no symptoms of respiratory infection and no exposure to relevant allergens for at least six weeks. Bronchial responsiveness did not change in those who required no medication or inhaled salbutamol only to control their symptoms, but was significantly improved in those who required continuous treatment with both beclomethasone and salbutamol (p = 0.03). The results suggest that non-specific bronchial responsiveness remains similar over long periods when exacerbating factors are not present and that treatment with beclomethasone may reduce hyperresponsiveness.